2011
DOI: 10.1109/tsmcb.2011.2112347
|View full text |Cite
|
Sign up to set email alerts
|

A Method to Measure the Relationship Between Biodynamic Feedthrough and Neuromuscular Admittance

Abstract: Biodynamic feedthrough (BDFT) refers to a phenomenon where accelerations cause involuntary limb motions, which can result in unintentional control inputs that can substantially degrade manual control. It is known that humans can adapt the dynamics of their limbs by adjusting their neuromuscular settings, and it is likely that these adaptations have a large influence on BDFT. The goal of this paper is to present a method that can provide evidence for this hypothesis. Limb dynamics can be described by admittance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(69 citation statements)
references
References 25 publications
0
69
0
Order By: Relevance
“…1 are shown for a much larger frequency range than used by Mayo, as the BDFT dynamics also show interesting features outside the 1-5 Hz frequency range [20]. The frequency range used by Mayo was limited and it is therefore likely that the model's quality will reduce outside this range.…”
Section: Discussion On the Mayo Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…1 are shown for a much larger frequency range than used by Mayo, as the BDFT dynamics also show interesting features outside the 1-5 Hz frequency range [20]. The frequency range used by Mayo was limited and it is therefore likely that the model's quality will reduce outside this range.…”
Section: Discussion On the Mayo Modelmentioning
confidence: 99%
“…Each task was trained before the experiment started. In earlier studies, it was shown that the neuromuscular admittance and BDFT strongly depend on these control tasks [21,20]. The three tasks combined with the three directions results in a 3x3 repeated-measures design, each condition was repeated 6 times.…”
Section: Experiments Designmentioning
confidence: 99%
See 3 more Smart Citations